Effects of Autologous Conditioned Plasma® (ACP) on the healing of surgically induced core lesions in equine superficial digital flexor tendon - van Weeren, René (2014)
Tendon pathologies are among the most common musculoskeletal disorders in horses. After damage the tendon repairs by forming disorganized scar tissue that is of inferior functional quality than normal tendon, leading to high re-injury rates. Many of the cur- rently available treatment modalities cannot significantly reduce this high recurrence rate. Autologous Conditioned Plasma (ACP, Arthrex Inc., USA) has been described in the literature as a leukocyte-reduced platelet concentrate. This blood product has been used in equine and human medicine for the treatment of tendon and ligament injuries. However, the effect of this therapeutical approach on tendon healing is unknown. Core lesions were surgically induced in the Superficial Digital Flexor Tendons (SDFT) of both fore- and hindlimbs in eight healthy horses. At days 7 and 15 after lesion induction one randomly assigned fore- and hindlimb was treated with ACP and the contralateral one with saline. This study used data from the forelimbs SDFTs only. Gray-scale and color Doppler ultrasonographic para- meters monitored throughout the study didn t differ significantly at any time point. Twenty-two weeks after the last treatment, the ACP tre- ated tendons presented a significantly lower concentration of sulphated glycosaminoglycans (GAGs) (p≤0.05) when compared to saline. Other compositional, biomechanical and histological parameters presented no significant differences. Our study indicates that 2 intra- tendinous ACP treatments (without anticoagulant) during the proliferative phase of healing in surgically induced tendon core lesions, have a limited effect on tendon healing when comparing ultrasonographic, biochemical, biomechanical and histological parameters with the control treatment. Long-term placebo controlled clinical trials with more horses are warranted to determine if this effect is clinically sig- nificant.